The Effect of Providing Educational Media on Anemia and Nutrition on the Prevention of Anemia in Young Women in Bekasi City - El Mahmudiyah, Regietta Neiva Fitriyah; Kurniasari, Ratih Kurniasari (Media Gizi Indonesia, 2024)
Adolescents need to pay attention to the fulfillment of their nutritional needs at this time because with this transition period there is an increase in the need for nutrients to support physical and psychological growth and development. One of the nutritional problems faced by adolescents is anemia. The prevalence of young women suffering from anemia in Bekasi City in 2020 is 26.4%. The purpose of this study was to determine the effect of providing educational media on anemia and nutrition on the prevention of anemia in young women in Bekasi City. This study was a pre-experimental study with pretest and posttest designs. The sample in this study was 60 young women who were divided into three groups with 20 young women in each group, each group had an intervention using different media, namely leaflet media, animated video, and QuizWhizzer game innovation media. The results of the paired t-test in the three groups showed a change in the increase in knowledge in each education group, with p-value in the leaflet group of 0.000, in the video animation group of 0.017, and the quiz whizzer game group of 0.012. Based on the results of this study, it can be concluded that the provision of educational media about anemia and nutrition has an influence on the prevention of anemia in young women.